Antimicrobial resistance of emerging foodborne pathogens: Status quo and global trends - Koluman, Ahmet; Dikici, Abdullah (Critical reviews in microbiology, 2013)
Emerging foodborne pathogens are challenging subjects of food microbiology with their antibiotic resistance and their impact on public health. Campylobacter jejuni, Salmonella spp. and Verotoxigenic Escherichia coli (VTEC) are significant emerging food pathogens, globally. The decrease in supply and increase in demand lead developed countries to produce animal products with a higher efficiency. The massive production has caused the increase of the significant foodborne diseases. The strict control of food starting from farm to fork has been held by different regulations. Official measures have been applied to combat these pathogens. In 2005 EU declared that, an EU-wide ban on the use of antibiotics as growth promoters in animal feed would be applied on 1 January 2006. The ban is the final step in the phasing out of antibiotics used for non-medical purposes. It is a part of the Commission's strategy to tackle the emergence of bacteria and other microbes resistant to antibiotics, due to their overexploitation or misuse. As the awareness raises more countries banned application of antibiotics as growth promoter, but the resistance of the emerging foodborne pathogens do not represent decrease. Currently, the main concern of food safety is counter measures against resistant bugs.